Easy trails around Shimla : day and overnight hikes - Bhasin, Raaja (Rupa New Delhi, 2016)
Raaja Bhasin paints a breathtakingly beautiful picture of treks around Shimla, which can be navigated by anyone with a reasonable level of fitness and more than a reasonable level of interest in the hills. Exhaustively researched and delightfully interspersed with beautiful photographs of tourist sites along the way and helpful tips to keep in mind while navigating these routes, Easy Trails around Shimla will appeal to every trekker, whether amateur or veteran.
Keywords: Simla Region (India) Guidebooks